(untitled) - Kolostova, Marianna (Aura musica, 2017)
The article reflects the personality and choral work of doc. PhDr. Tibor Sedlicky, CSc., the representative of ``true'' tradition of music education teaching and choir singing in Slovakia. Attention is drawn to the diversity and proportional balance of his pedagogical, conductorial, conceptual, artistic and publishing work focused primarily on choral-singing activities. It evaluates his contribution to the development of choral art in Slovakia.
Keywords: personality; choir singing; work: pedagogical; conductorial; conceptual; artistic; publishing